Joint venture versus non-joint venture projects in the UAE construction industry: a comparison of the usage of project management practices and performance. (11th October 2019) - Bashir, Hamdi; Ojiako, Udechukwu; Garbie, Ibrahim
The purpose of this paper is to report on a study comparing joint venture and non-joint venture projects in terms of their performance and usage of project management practices. Data were obtained from project managers at 99 contracting organisations in the United Arab Emirates (UAE) construction industry. The results show an agreement between the two types of project in the usage level of 35 out of 40 different practices associated with the ten knowledge areas articulated in the Project Management Institute (PMI) Project Management Body of Knowledge (PMBOK) Guide (PMI, 2017). However, joint venture construction projects had higher usages of four cost-and procurement-related practices compared to non-joint venture construction projects. The results also show that although they are associated with increased risks due to the involvement of partners, generally the overall performance of joint venture construction projects is comparable with that of non-joint venture construction projects. The findings of this study could be of value to organisations that are planning to form joint venture projects in the UAE and other countries with similar environments.